KEANEKARAGAMAN JENIS SEMUT (Formicidae) DI HUTAN ALAM SEKUNDER DESA SEPANDAN KECAMATAN BATANG LUPAR KABUPATEN KAPUAS HULU - Gusmasri, Rahmat; Anwari, M Sofwan; Prayogo, Hari (JURNAL HUTAN LESTARI, 2018)
Ants (Formicidae) are a type of insect that has a fairly stable population throughout the season and year. Its large and stable amount makes ants one of the important insect colonies in the ecosystem. Ants are often used as bio-indicators in environmental assessment programs. This study aims to record the diversity of ant species (Formicidae) in secondary natural forest areas in Sepandan Village, Batang Lupar District, Kapuas Hulu District based on altitude from sea level. The method used is purposive sampling by using a trap in each tree in the path of observation, this observation uses three paths based on the height of the observation place, the first line at an altitude of 100 meters above sea level, the second track at an altitude of 200 meters above sea level and the third line at an altitude of 300 meters above sea level. The trap used is Pit Fall Traps trap on the ground surface and Fly Sheet on the tree. Ants who were captured at an altitude of 100 masl were 1,025 individuals consisting of 9 genera and 13 species, at an altitude of 200 masl of ants that were successfully captured as many as 4,228 individuals consisting of 8 genera and 9 species, while at an altitude of 300 masl ants were captured as much as 2,940 individuals consisting of 15 genera and 21 species. The dominant species at an altitude of 100 meters above sea level is Crematogaster obscura, at an altitude of 200 meters above sea level dominated by the species Crematogaster reticulata, and at an altitude of 300 meters above sea level this location is dominated by Acanthomyrmex ferox species. Diversity index of ant species at an altitude of 100 masl of 0.709, at an altitude of 200 meters above sea level of 0.565 and at an altitude of 300 meters above sea level of 1.131 with a total diversity value of 0.801.Keyword: Ant, Diversity, Secondary Natural Forests